Gene flow in, and mating system of, Rhododendron simsii in a nature reserve in subtropical China. (3rd October 2016) - Hahn, Christoph Z.; Michalski, Stefan G.; Durka, Walter
Abstract : Mating system and gene dispersal distances are two important characteristics that govern the distribution of genetic variation within species. Genetic variation is an important resource for adaptation, but also allows insight into a species reproductive biology. As the reproductive biology is species specific, general inferences across species may be inaccurate and for many species not much is known about the details of gene flow and mating, especially in species‐rich ecosystems such as the subtropics. We characterised the mating system and determined historical and current gene flow distances in Rhododendron simsii using microsatellite markers. Adult individuals and seeds were sampled in a near‐natural nature reserve in southeast China. We examined the fine‐scale spatial genetic structure (SGS), kinship coefficients, outcrossing rates and biparental inbreeding coefficients. Furthermore, we estimated pollen dispersal distances using paternity analysis. We found high outcrossing rates and significant biparental inbreeding. Population differentiation was low while observed heterozygosity and allelic richness were high. Estimates of historical and current gene flow were similar, indicating that genes are on average dispersed over distances of between 10 and 20 m. Paternity analyses suggest frequent mating among neighbouring individuals. We conclude that R. simsii is predominantly, but not obligately outcrossing. Moderate amounts of biparental inbreeding and overall low fine‐scale SGS indicate that mating among related individuals is common, but does neither lead to pronounced population differentiation nor to strong aggregation of related individuals. Most likely, gene flow distances in this species are affected by its flowering phenology. Mass‐flowering, pollen/pollinator limitation and gravity/wind dispersal of seeds in concert cause short gene dispersal distances. Lastly, population genetic descriptors suggest that R. simsii in the study area represents a large, well connected population in which large amounts of genetic variability are maintained.